Manajemen Mutu Pendukung Akademik Sekolah Dasar Berbasis Religi - Imron, Ali (Pendidikan Dasar, 2009)
Abstract: The research aim is to deeply describe the quality management of academic supporting system on religion-based primary school, that include quality management of student affairs, human resource, infrastructure and facility, financial, and community participation. The research used qualitative approach with phenomenology orientation and multi-case design. The research data were collected through participatory observations, in-depth interviews, and documentary study. Individual case data were analyzed using path model developed by Miles and Huberman (1992)  combined by multi cases by Yin (2002). The research found, student affairs quality management is the processing of student input to be quality output. Educational staff quality management includes the activities of recruitment, deployment, competence improvement, reward provision for educational staff so that they provide quality contribution to the educational processes. The quality management of infrastructure and facilities is the management of infrastructure and facility readiness to be utilized to support both academic and nonacademic implementation. The financial quality management is endeavor for fund raising and budgeting in qualified and selected manner to support educational quality and activities. The quality management for community participation is the activities for gathering, involving, and actuating community potentials, particularly students’ parents, in supporting educational processes.